Reparations and Anti-Black Racism : a Criminological Exploration of the Harms of Slavery and Racialized Injustice. - Nurse, Angus (Bristol University Press, 2021)
Police shootings and incarceration inequalities are two examples of the legacy of slavery in the US and UK. Offering a criminological exploration of the case for slavery and anti-black racism reparations in the context of enduring harms and differential treatment of black citizens, this book refutes the policy perspectives that oppose reparations.